1969
DOI: 10.1002/1097-4679(196910)25:4<455::aid-jclp2270250435>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Therapist goals, patient aims and patient satisfaction in psychotherapy

Abstract: PROBLEMThe goals and wants of the participants in psychotherapy are potentially significant factors in the therapeutic exchange. The goals that a therapist sets with a particular patient can be considered indices of the direction in which he seeks to influence the experience of the patient. What the patient says she wants from therapy might be expected to influence what she reports receiving. This study explored the therapeutic perspectives of patients and therapists by determining the cluster dimensions of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

1974
1974
1986
1986

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…Similarly, it is no surprise that feeling as though one's feelings are understood enhances continuance, as patient perceived "accurate empathy" has been associated with a variety of positive outcome measures [28]. The final significant factor, satisfaction with the initial visit, also has previous research validation for its positive role in compliance measures, including clinic attendance [5,23,. As in other studies of short term therapy, most patients in this study indicated high satisfaction [29,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, it is no surprise that feeling as though one's feelings are understood enhances continuance, as patient perceived "accurate empathy" has been associated with a variety of positive outcome measures [28]. The final significant factor, satisfaction with the initial visit, also has previous research validation for its positive role in compliance measures, including clinic attendance [5,23,. As in other studies of short term therapy, most patients in this study indicated high satisfaction [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…With few exceptions, however, the specific relationship of patient requests and adherence behavior has not been carefully evaluated [ 13,[18][19][20][21][22][23][24][25] . This paper examines the association between patients' requests, outcome of initial sessions and return for further therapy.…”
mentioning
confidence: 99%
“…In psychotherapy studies, it has been shown that the therapists' convictions and direction can influence the therapeutic outcome. 19 Other studies have shown that greater perceived involvement led to greater patient satisfaction.f This field requires further investigation, particularly with the chronic patient, to determine the correct balance between perceived and actual involvement in goal setting.…”
Section: Goal Categoriesmentioning
confidence: 99%
“…In order to place the client's ratings in perspective, the therapist was asked to answer the same three questions from his own point of view. Past research (Strupp, Fox, & Lesser, 1969;Hill, 1969;Feifel & Eells, 1963)led us to expect only modest correlations between answers of clients and their therapists. Also, the two face a somewhat different task.…”
mentioning
confidence: 98%